Assessment of the Phytochemical Composition, Antioxidant Activity, and In-vitro Cytotoxic Effects of Begonia malabarica on Pancreatic Cancer Cell Line (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The study assesses the biological properties of methanolic extracts derived from the leaves, stems, and roots of Begonia malabarica, a native plant species in the mountainous area of southern India. The GC-MS was used to analyze the phytochemicals in the solvent from Begonia malabarica that had been extracted with methanol. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and as reference solution is ascorbic acid. The cytotoxicity activity was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) approach. The GC-MS analysis effectively revealed 35 distinctive phytomolecules. The primary constituents, namely tert-butylbenzene (23%), 2-methylnaphthalene (6.2%), ethyl ester of octadecanoic acid (0.9%), and (Z,Z)-9,12-octadecadienoic acid (0.9%), are noted. The results, the methanolic extracts from B. malabarica are antioxidants that have significant levels (P < 0.05) of DPPH radical scavenging activities at different doses. The detected radical scavenging activities exhibited a higher proportion in the stem of B. malabarica. The IC50 values for the methanolic extracts were found to be 0.77 mg/ml, 0.49 mg/ml, and 0.68 mg/ml, respectively. The MTT analysis demonstrated that the methanolic extracts exhibited a considerable increase in cytotoxic activity against the pancreatic cancer (PANC-1) cell line, resulting in a cell viability percentage of 69.63% at a concentration of 31.25µg/ml. These findings confirm the possible biological effects of B. malabarica and its prospective use in different pharmaceutical pursuits in the future.